Common Heritage of Mankind Beyond Treaty Provisions: Customary or General Principle? - Merdekawati, Agustina; Triatmodjo, Marsudi; Hasibuan, Irkham Afnan Trisandi (UI Scholars Hub, 2024)
The Common Heritage of Mankind (CHM) has become a prevalent principle adopted in international treaties governing objects and resources situated beyond national jurisdictions. Despite this widespread adoption, it is still a subject of debate whether it constitutes something more than a mere treaty provision that only binds state parties. This paper aims to analyze the position of CHM in the sources of international law, with a focus on analyzing its existence as a customary norm and a general principle of international law. There has been no international dispute involving CHM, which leaves the question of its position in international law as it was never clarified by international court judges. This paper seeks to explore whether it would be legitimate for international courts to regard CHM as a law in settling disputes involving parties that are not bound to the relevant international treaties adopting CHM. The research was done normatively by assessing the historical and contemporary facts that could help clarify the position of CHM in international law. The research finds that CHM can be regarded as both a customary norm and a general principle of international law. CHM begins as a general principle rooted from natural law, which is then followed by consistent practices and opinio juris, indicating its acceptance as a customary norm. This paper argues that it would be legitimate for international courts to regard CHM as a law in resolving disputes relating to CHM objects irrespective of the parties’ involvement in the relevant international treaties.